Management of the Failed First Revision ACL Reconstruction: Clinical Outcomes of Nonsurgical Management Versus Second Revision ACL Reconstruction From the SANTI Group. Issue 12 (October 2022) - Fradin, Thomas; Saithna, Adnan; Haidar, Ibrahim M.; Rayes, Johnny; El Helou, Abdo; Ngbilo, Cedric; Pioger, Charles; Vieira, Thais Dutra; Hopper, Graeme P.; Sonnery-Cottet, Bertrand
Background: The optimum management strategy after failure of revision anterior cruciate ligament reconstruction (RACLR) is not clearly defined. The literature evaluating differences in outcomes between surgical and nonsurgical management is sparse. Purpose/Hypothesis: The purpose was to evaluate the outcomes of surgical versus nonsurgical management of failed first RACLR. It was hypothesized that the long-term clinical outcomes of second RACLR would be superior with respect to knee stability, return to sport, and patient-reported outcome measures when compared with nonsurgical treatment. Study Design: Cohort study; Level of evidence, 3. Methods: Patients who experienced failure of first RACLR were evaluated. All participants followed the same rehabilitation protocol regardless of whether they underwent nonsurgical treatment or a second RACLR. Follow-up comprised regular clinical review and a standardized telephone interview at the end of the study period. Patient-reported outcome measures were recorded at the final follow-up. Results: A total of 41 patients with a mean follow-up of 104 ± 52.7 months (range, 40-140 months) were evaluated. Of these, 31 underwent a second RACLR, and 10 patients chose nonsurgical treatment. There was a high rate of return to sport in both groups, but patients undergoing second RACLR had significantly better Tegner (6.35 vs 4.8; P = .012), Lysholm (88.5 vs 78.3; P = .0353), Knee injury and Osteoarthritis Outcome Score (KOOS) Quality of Life (72.6 vs 56.3; P = .0490), and KOOS Sport and Recreation scores (81.4 vs 62.5; P = .0033). Significantly more patients undergoing second RACLR achieved the Patient Acceptable Symptom State for KOOS Sport and Recreation than those who underwent nonsurgical management (74.2% vs 30%; P = .015). The most important predictor of failure to achieve a good/excellent Lysholm score in multivariate analysis was nonsurgical management ( P = .0095). Conclusion: Both second RACLR and nonsurgical management of failed first RACLR were associated with high rates of return to sport. However, second RACLR was associated with significantly better functional outcome scores with respect to Tegner, Lysholm, KOOS Quality of Life, and KOOS Sport and Recreation scores compared to nonsurgical management. In addition, nonsurgical treatment was the only significant predictor of failure to achieve a good/excellent Lysholm score at the final follow-up, and this was likely a function of inferior knee stability in that group.